A Tool to Characterize the Electrical Influence of the Thermal and Mechanical Behaviors of Materials of Optics for CPV applications. (27th June 2017) - Ritou, Arnaud; Raccurt, Olivier; Voarino, Philippe; Besson, Pierre; Baudrit, Mathieu
ABSTRACT: Concentrating Photovoltaics (CPV) field aims to integrate expensive high efficiency multi-junction cells into modules with low cost concentrating optics. The choice of the optics depends on different factors: easiness of fabrication and integration process, added costs, optical efficiency and the profile of the spot uniformity reaching the cell. Indeed, previous work has shown a dependence between electrical performance and spectral and spatial uniformities of the light on the cell. To analyze it, a solar CPV test bench is developed at CEA-INES facilities. Lens and cell temperature can be applied separately, in order to evaluate independently different test conditions, while electrical or optical parameters are recorded. The present work shows how temperature and mechanical variations on first stage concentrating optic affects module performances. Several optics and materials are compared, in order to present the tool capabilities.